Augmented Reality in The Classroom: Revolutionizing Vocabulary Teaching for High School Language Learners - Idul, Muhammad; Syaiful, Syaiful (Institut Agama Islam Negeri Parepare, 2024)
This literature review examines the integration of Augmented Reality (AR) in high school language education for vocabulary teaching. It analyzes current research to explore AR's benefits, challenges, and implications for vocabulary mastery. Key findings include: (1) AR's interactive features enhance student engagement and vocabulary retention; (2) AR provides contextualized learning experiences, improving practical application of vocabulary; (3) Effective AR implementation requires carefully designed content and user-friendly interfaces; (4) Challenges include content development, teacher training, and technical limitations. The study proposes solutions to these issues and offers insights for leveraging AR to enhance vocabulary development in high school language education.